The European treatment of severe atopic eczema in children taskforce (TREAT) survey. (10th October 2013) - Proudfoot, L.E.; Powell, A.M.; Ayis, S.; Barbarot, S.; Baselga Torres, E.; Deleuran, M.; Fölster‐Holst, R.; Gelmetti, C.; Hernández‐Martin, A.; Middelkamp‐Hup, M.A.; Oranje, A.P.; Logan, K.; et al.
Summary Background There is a paucity of evidence for the use of systemic agents in children with atopic eczema refractory to conventional therapy, resulting in considerable variation in patient management. Objectives The European TREatment of severe Atopic eczema in children Taskforce (TREAT) survey was established to collect data on current prescribing practice, to identify factors influencing the use of specific systemic agents, and to inform the design of a clinically relevant intervention study. Methods Consultant physician members of the paediatric dermatology societies and interest groups of eight European countries were invited to participate in a web‐based survey. The multiple‐response format questionnaire collated data on clinical practice in general, as well as detailed information on the use of systemic agents in refractory paediatric atopic eczema. Results In total, 343/765 members (44·8%) responded to the invitational emails; 89·2% were dermatologists and 71% initiate systemic immunosuppression for children with severe atopic eczema. The first‐line drugs of choice were ciclosporin (43·0%), oral corticosteroids (30·7%) and azathioprine (21·7%). Ciclosporin was also the most commonly used second‐line medication (33·6%), with methotrexate ranked as most popular third choice (26·2%). Around half of the respondents (53·7%) replied that they routinely test and treat reservoirs of cutaneous infection prior to starting systemic treatment. Across the eight countries, penicillins were the first‐line antibiotic of choice (78·3%). Conclusions In the absence of a clear evidence base, the European TREAT survey confirms the wide variation in prescribing practice of systemic immunosuppression in refractory paediatric atopic eczema. The results will be used to inform the design of a randomized controlled trial relevant to patient management across Europe.